A study of the role of diagnostic laparoscopy in 25 cases of acute abdomen - Ram, Kamlesh; Chandana, Sanjog (International Surgery Journal, 2017)
Background: Acute abdomen is associated with patient discomfort and diagnostic challenges. Diagnostic laparoscopy is a tool which can help in providing diagnosis and treatment. This study is aimed to use laparoscopy as diagnostic and therapeutic procedure. It can avoid unnecessary open procedure, provide early discharge, and decrease patient discomfort. Methods: A case study of 25 cases of acute abdomen was done. All cases were initially evaluated with ultrasonography abdomen and abdominal X-ray and diagnostic laparoscopy was done. Therapeutic procedures were done according to pathology encountered. All patients were followed up 1 year from discharge Results: A total 25 cases were used; appendicectomy was done in 12 patients, adhesiolysis in 3 patients, peptic perforation repair done in 3 patients. Drainage of fluid done in 1 patient. Omental biopsy was taken in 1 patient. Marsupialisation of left ovary done in 1 patient. 8% cases required open surgery. Open right hemicolectomy and resection anastomosis, open enteric perforation repair was done in 1 patient each. 52% cases were discharged within 2 days. 10% patient required stay for 6 days. Conclusions: Diagnostic laparoscopy can be used in acute abdomen. It avoids unnecessary laparotomy and helps in diagnosis in which radiological findings are equivocal. Post-operative recovery is fast in compare to open procedure.